2023
DOI: 10.1007/s10578-023-01514-z
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Pharmacotherapy in the Management of Children with Autism Spectrum Disorder at a Public Hospital in KwaZulu-Natal

Abstract: This study presents an overview of prescribing patterns and provides insight into the current management practice for the core symptoms and comorbidities of ASD in children. A quantitative retrospective study was conducted at a public hospital in KwaZulu-Natal, South Africa by reviewing patient files of children diagnosed with ASD and meeting the inclusion criteria for the study. A descriptive analysis of data was done to identify treatment trends and patient therapeutic outcomes. A total of 181 children met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In this study, 37 of the 67 children and adolescents were diagnosed with ADHD (55.2%), which is in keeping with findings of another study at a paediatric neurology public hospital in KwaZulu-Natal, which reported a 57% prevalence rate of ADHD. 70 The finding in this study that 29.9% of patients had a comorbid diagnosis of epilepsy is consistent with other studies such as 30.0% prevalence of comorbid seizure disorders in ASD in a study by Maniram et al in 2023. 70 Varying rates of epilepsy have been found and other studies have reported different rates; for example, Mannion et al found that 10.1% of children and adolescents with ASD had a comorbid diagnosis of epilepsy.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, 37 of the 67 children and adolescents were diagnosed with ADHD (55.2%), which is in keeping with findings of another study at a paediatric neurology public hospital in KwaZulu-Natal, which reported a 57% prevalence rate of ADHD. 70 The finding in this study that 29.9% of patients had a comorbid diagnosis of epilepsy is consistent with other studies such as 30.0% prevalence of comorbid seizure disorders in ASD in a study by Maniram et al in 2023. 70 Varying rates of epilepsy have been found and other studies have reported different rates; for example, Mannion et al found that 10.1% of children and adolescents with ASD had a comorbid diagnosis of epilepsy.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Maniram et al report that less than half (44%) of patients were being seen by speech and/or occupational therapy, of whom, 23% were recommended by the prescriber of the pharmacological management. 70 With regards to medication in this study, all those with ASD were on psychotropic medication and 40 patients (59.7%) were on more than one, the most widely used being anticonvulsants (59.7%), risperidone (53.7%), and methylphenidate (28.4%). This is consistent with a systematic literature review by Ritter et al, which found that most of the youth with ASD were taking two or more medications, psychotropic or non-psychotropic, simultaneously.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations